FREQUENCY OF PULMONARY HYPERTENSION IN POST TUBERCULOSIS PATIENTS - REHMAN , AU; HUSSAIN , S; ULLAH , F; HABIB , M; SIKANDAR , S; MASOOD, MA (Biological and Clinical Sciences Research Journal, 2024)
Pulmonary arterial hypertension (PAH) is a severe complication that can develop in patients with a history of pulmonary tuberculosis (PTB), leading to increased morbidity and mortality. This study aimed to determine the frequency and associated risk factors of PAH in post-TB patients, with a focus on age, gender, BMI, and duration since TB diagnosis. Objective: To assess the frequency of PAH and identify potential risk factors in post-TB patients, providing insights to guide improved screening and follow-up practices. Methods: A cross-sectional study was conducted on 108 post-TB patients at the Department of Pulmonology, Hayatabad Medical Complex, Peshawar from January 2024 to July 2024. PAH was diagnosed using echocardiography, with pulmonary arterial pressure (PAP) thresholds set above 20 mmHg. Data were analyzed to assess associations between PAH and variables including age, gender, BMI, and time since TB diagnosis. Results: The study found a 35.2% prevalence of PAH among post-TB patients. Older age and longer duration since TB diagnosis were significantly associated with higher PAH frequency, while gender and BMI were not significantly associated with PAH risk. Conclusion: It is concluded that PAH is a common complication in post-TB patients, particularly among older individuals and those further removed from their TB diagnosis. These findings underscore the need for routine PAH screening in high-risk post-TB patients to enable timely intervention and improve outcomes.